2017
DOI: 10.1371/journal.pone.0186304
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the rate of cesarean delivery on maternal request through institutional and policy interventions in Wenzhou, China

Abstract: The objective of this study was to evaluate the effect of institutional and policy interventions on reducing the rate of cesarean delivery on maternal request (CDMR) in Wenzhou, China. Institutional interventions included health education, painless delivery introduction, and doula care. Additionally, a series of health policies were developed by the Chinese central and local governments to control cesarean section rates, mostly through controlling CDMR rates. We conducted a pre-/post-intervention study using 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…[104][105][106] Indeed, recent evidence from specific sites and regions in China suggests that using multi-level interventions that include change in government policy, financial incentives, local benchmarking, education of staff and of service users, provision of doula support and access to pain relief, can limit the rise in CS rates. 107,108…”
Section: Implementing Change Effectivelymentioning
confidence: 99%
“…[104][105][106] Indeed, recent evidence from specific sites and regions in China suggests that using multi-level interventions that include change in government policy, financial incentives, local benchmarking, education of staff and of service users, provision of doula support and access to pain relief, can limit the rise in CS rates. 107,108…”
Section: Implementing Change Effectivelymentioning
confidence: 99%
“…On the other hand, two Chinese retrospective observational studies suggested that multifaceted interventions involving government policy, finical incentives, local benchmarking, health education for health professionals and pregnant women, doula care, and access to labor analgesia could decrease the CS use effectively [40,41]. In a retrospective study at a large maternity hospital in Shanghai, Liu et al compared CS rates before and after the implementation of a multifaceted intervention [41], which included government and hospital measures.…”
Section: Discussionmentioning
confidence: 99%
“…NA not applicable changed by institutional interventions and government policy [40]. Institutional interventions consisted of three aspects: providing health education to mothers and their families; training obstetricians and midwives, issuing CS indications and guidelines, and conducting audits every month; promoting labor analgesia and doula care by midwives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most obstetric centers in China cannot meet the rising expectations of pregnant women, such as lacking the company of family members especially husband, analgesia, or emotional support in labor [3,4] . In recent years, a few Chinese hospitals have started to control the unusually high CD rates with health education, painless delivery, doula delivery and psychological comforting and training programs for midwives and obstetricians [17] . In our birth center, with the help of NPLD program, NA was available for women who requested in to relieve labor pain from May 1, 2015.…”
Section: Discussionmentioning
confidence: 99%